COGNITIVE AND AFFECTIVE OUTCOMES OF STRUCTURED AND ANDRAGOGICAL APPROACHES IN TECHNOLOGY-BASED LANGUAGE LEARNING: A CROSSOVER STUDY - Khadijah Ramadhanti; Syahrul Ramadhan; Yuli Tiarina (JURNAL KONFIKS, 2026)
The proliferation of digital technology in higher education language learning requires instructional approaches that align with the characteristics of adult learners. This study examines the comparative cognitive and affective outcomes of structured and andragogical technology-based approaches on language proficiency, motivation, and digital engagement using a within-subject crossover design. Thirty students at STKIP YDB Lubuk Alung were assigned to two counterbalanced groups: Group A (n = 15) followed a structured-then-andragogical sequence, while Group B (n = 15) followed the reverse, with a one-week washout period between treatments. Paired t-tests demonstrated that both approaches produced significant language proficiency gains (p < .001), yielding large effect sizes for structured instruction (d = 2.73; gain = +18.67 points) and andragogical learning (d = 2.47; gain = +19.70 points), with no statistically significant difference between them (p = .508, d = 0.12), a result confirmed by the Wilcoxon signed-rank test (p = .600). In contrast, andragogical instruction generated significantly higher motivation (M = 4.27; d = 2.54) and digital engagement (M = 4.18; d = 2.19) than structured instruction (p < .001). A near-zero correlation between engagement scores across the two conditions (r = .067) indicates that each approach activates qualitatively distinct engagement mechanisms. Significant and symmetric carry-over effects across both conditions (p < .001) suggest that sequential exposure to contrasting technology-based approaches yields cumulative learning benefits. These findings support a hybrid instructional model that combines the cognitive scaffolding of structured instruction with the affective autonomy of andragogical learning.